VD_FINDINFO HC / 2011 / 240 vom 18. Februar 2011 - VD Tribunal cantonal (2011)
SALAIRE, CONTRAT DE TRAVAIL, RÉSILIATION, PREUVE | 8 CC, 19 al. 1 CCT-Second oeuvre, 19 al. 3 CCT-Second oeuvre, 20 al. 1 CCT-Second oeuvre, 322 al. 1 CO, 322 CO, 337d al. 1 CO, 337d CO, 452 al. 1ter CPC, 452 al. 2 CPC, 46 LJT